Improving Employee Performance: A Study of The Influence of Motivation Sincerity Discipline and Work Environment - Bezisokhi Laoli; Lase, Famahato Lase; Eka Septianti Laoli (International Journal of Contemporary Studies in Education, 2024)
Employee performance can be improved with various efforts. The aim of this research is to reveal the influence of work motivation (X1), sincerity work (X2), work discipline (X3), and work environment (X4) on employee performance (Y), using associative strategy quantitative research methods. The research location was the Nias Regency Education Office, the research population was all 138 employees and the sample was drawn by purposive sampling of 40 people. Data was collected using a closed questionnaire and analyzed using inferential statistics using multiple linear regression techniques. The results of the study concluded that there is a significant influence in part between work motivation, sincerity, discipline and the environment on employee performance. Every increase in work motivation, sincerity, discipline and environment by 1,00% will be followed by an increase in employee performance by 13,207%. It is recommended to leaders and organizations to increase motivation, sincerity, discipline and work environment in order to achieve better performance.